PENGARUH EKSPEKTASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP DUKUNGAN CORPORATE SOCIAL RESPONSIBILITY - Khairiansyah Khairiansyah; Siti Mutmainah (Diponegoro Journal of Accounting, 2012)
Corporate Social Responsibility (CSR) is often considered the core of business ethics, which means that companies not only have economic obligations and legal (meaning to a shareholder), but also the obligations of other parties concerned (stakeholders) that its reach beyond economic and legal obligation. This study aims to determine and analyze the expectations of economic dimension, legal dimension and ethical dimension of CSR toward CSR Support in faculty of economics and business Diponegoro University. Sample of this study is accounting student at the Faculty of Economics and Business, Diponegoro University Semarang obtained as many as 125 respondents. This research uses multiple regression analysis to determine the effect of expectations ecoomic, legal and ethical-philanthropic dimension of CSR to support CSR. Survey results revealed economic expectation, legal and ethical expectation expectation is partially positive and significant effect on CSR support.